A dynamic multi-objective approach for the reconfigurable multi-facility layout problem. (January 2017) - Azevedo, Maria Manuela; Crispim, José António; Pinho de Sousa, Jorge
Highlights: Extends the classic FLP from a new perspective, by design and reconfigure several facilities simultaneously. Very important to bring flexibility and agility to companies on responsiveness to market changes. Layout analysis and reconfiguration at two integrated levels; globally, all facilities and locally, each facility. A new objective, Unsuitability combine existing location characteristics with requirements of departments. A problem inspired and applied on a real case of automotive industry. Abstract: The multi-facility layout problem involves the physical organization of departments inside several facilities, to allow flexible and efficient operations. This work studies the facility layout problem in a new perspective, considering a group of facilities, and two different concerns: the location of departments within a group of facilities, and the location of departments inside each facility itself. The problem is formulated as a Quadratic Programming Problem with multiple objectives and unequal areas, allowing layout reconfigurations in each planning period. The objectives of the model are: the minimization of costs (material handling inside facilities and between facilities, and re-layout); the maximization of adjacency between departments; and the minimization of the "unsuitability" of department positions and locations. This unsuitability measure is a new objective proposed in this work, to combine the characteristics of existing locations with the requirements of departments. The model was tested with data from the literature as well as with a problem inspired in a first tier supplier in the automotive industry. Preliminary results show that this work can be viewed as an innovative and promising integrated approach for tackling real, complex facility layout problems.